Ruminal Ciliate (Ciliophora, Trichostomatia) Biota of European Roe Deer (Capreolus capreolus) in Kastamonu - Gürelli, Gözde; Mutlu, Ekrem (Commagene Journal of Biology, 2024)
This study investigated the ruminal ciliate biota of European roe deer (Capreolus capreolus) in Kastamonu. Only one species, Entodinium dubardi (Ophryoscolecidae, Trichostomatia), was identified from the ruminal contents of twelve (70.6% prevalence) of seventeen roe deers. Five of seventeen roe deer had no ciliates. E. dubardi was determined for the first time from the ruminal content of roe deer in Türkiye. The average ciliate concentration was 17.5 ± 27.0 × 104 cells mL–1. Min.–max. values ranged from 0 to 87 × 104 cells mL–1.
Keywords: Cervidae; Entodinium dubardi; Ophryoscolecidae; microorganism; ecosystem; Animal Diet and Nutrition; Cervidae; Entodinium dubardi; Ophryoscolecidae; mikroorganizma; ekosistem; Hayvan Diyeti ve Beslenme; Animal Systematics and Taxonomy; Hayvan Sistematiği ve Taksonomi